Implementation “Kuliah Keahlian” in Business Information Management and Multimedia Vocational Education Brawijaya University - Sovia Rosalin (Program Pendidikan Vokasi Universitas Brawijaya, 2015)
The advancement of education in Indonesia, especially Universities tinged with a large problem. One of these problems is the lack of relevance between universities and business and industry (DUDI). In order to overcome these problem, Vocational Education at UB then has designed program the so-called “Kuliah Keahlian”. The implementation of KK aims to provide students majoring in Business and Information Management Expertise Multimedia an opportunity to know the business world and the real world industry (facts), to understand what is really happening in the world of business and industry, to apply the theories that have been obtained in the regular course (KR), and to improve their confidence for facing the fact that it turns out they are capable and highly master practical jobs that exist in the DUDI and to increase public trust in the ability and mastery of vocational program graduates. This study is qualitative whose result shows that the implementation of KK is quite well-done and it has given positive impact to the students which is shown by the increasing number of students who already have their own business (52% of students) after the implementation of KK.